Enhanced EGFR Targeting Activity of Plasmonic Nanostructures with Engineered GE11 Peptide. Issue 23 (25th September 2017) - Biscaglia, Francesca; Rajendran, Senthilkumar; Conflitti, Paolo; Benna, Clara; Sommaggio, Roberta; Litti, Lucio; Mocellin, Simone; Bocchinfuso, Gianfranco; Rosato, Antonio; Palleschi, Antonio; Nitti, Donato; Gobbo, Marina; et al.
Abstract: Plasmonic nanostructures show important properties for biotechnological applications, but they have to be guided on the target for exploiting their potentialities. Antibodies are the natural molecules for targeting. However, their possible adverse immunogenic activity and their cost have suggested finding other valid substitutes. Small molecules like peptides can be an alternative source of targeting agents, even if, as single molecules, their binding affinity is usually not very good. GE11 is a small dodecapeptide with specific binding to the epidermal growth factor receptor (EGFR) and low immunogenicity. The present work shows that thousands of polyethylene glycol (PEG) chains modified with lysines and functionalized with GE11 on clusters of naked gold nanoparticles, obtained by laser ablation in water, achieves a better targeting activity than that recorded with nanoparticles decorated with the specific anti‐EGFR antibody Cetuximab (C225). The insertion of the cationic spacer between the polymeric part of the ligand and the targeting peptide allows for a proper presentation of GE11 on the surface of the nanosystems. Surface enhanced resonance Raman scattering signals of the plasmonic gold nanoparticles are used for quantifying the targeting activity. Molecular dynamic calculations suggest that subtle differences in the exposition of the peptide on the PEG sea are important for the targeting activity. Abstract : Cell targeting activity of nanostructures is of great importance for biotechnology applications. Functionalization with antibodies is a natural choice but they can show adverse immunogenic activities and their cost is usually very high. Here it is shown that, for epidermal growth factor receptor targeting, thousands of small peptides with engineered functionalization and organized on naked gold nanoparticles offer an alternative with higher sensitivity and specificity.